Having a word with Angus Graham : at twenty-five years into his immortality - Defoort, Carine, 1961-; Ames, Roger T., 1947- (Albany, NY : State University of New York, 2018)
Critical reflections on the work of Angus Charles Graham, renowned Western scholar of Chinese philosophy and sinology. This volume engages with the works and ideas of Angus Charles Graham (1919-1991), one of the most prominent Western scholars of Chinese philosophy, at the twenty-fifth anniversary of his passing. Over a professional career of more than thirty years, Angus Graham produced an impressive amount of scholarship on a wide array of topics, ranging from Chinese grammar and philology to poetry and philosophy. His combination of rigorous scholarship and philosophical originality has continued to inspire scholars to tackle related research topics, and in so doing, has required of them a response to his views. This book illustrates the range of scholarship still elaborating upon, disagreeing with, and reacting to Graham's work on Chinese thought, philosophy, philology, and translation.
Criticism for not sacrificing one hair to obtain the worldCynical appraisal of the ideal of abdication; By benefiting the world, one deserves to benefit from it; One Superficial Follower: â#x80;#x9C;Yang Zhuâ#x80;#x9D; in the Liezi; Conclusion; Notes; 9 Reconstructing A.C. Grahamâ#x80;#x99;s Reading of Mencius on xing?: A Coda to â#x80;#x9C;The Background of the Mencian Theory of Human Natureâ#x80;#x9D; (1967); Sharing a Hobby Horse; Setting the Problem; Angus Graham and the Narrative Interpretation of xing; Grahamâ#x80;#x99;s Initial Developmental Understanding of the Mencian xing ; Grahamâ#x80;#x99;s Evolving Understanding of xing.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 23, 2018).
JSTOR
Keywords: Graham, A. C; Zhuangzi; Zhuangzi; Philosophy, Chinese; Philosophie chinoise; PHILOSOPHY -- Eastern; Philosophy, Chinese